Characterization of an efflux pump system, in Clostridium difficile - Espinola Lopez, Jose (Kansas State University, 2017)
Clostridium difficile, a gram-positive, anaerobic bacterium, is a major cause of antibiotic-related diarrhea and pseudomembraneous colitis. In the last decades, C. difficile has emerged as a major threat because of its tendency to cause frequent and severe disease. Because of the severity of the infection and its high rate of recurrence, there is a significant financial burden on healthcare systems. Antibiotic treatments are a primary risk factor for the development of C. difficile infection because they disrupt the normal gut flora in the host, enabling the antibiotic resistant bacterium to colonize the colon. Most of the resistance mechanisms in C. difficile reported to date can be classified as either antibiotic-degrading enzymes or modification of target sites. Another mechanism that can contribute to antibiotic resistance in C. difficile is the extrusion of antimicrobial compounds by efflux pumps. The goal of this project was to provide initial insights into the roles and mechanisms of a putative efflux pump complex. To do this, a number of experiments were designed to provide information about the structures, localization, and functions of this protein complex. It was determined that acidic pH conditions and a small number of antimicrobials, including inorganic compounds, organic compounds, fungicides, and antibiotics, inhibit growth of a C. difficile mutant lacking this pump system. Interestingly, higher NaCl in the medium and alkaline pH seem to promote the growth of a C. difficile mutant lacking this pump or, surprisingly, only inhibit growth of the wild type strain. The experiments performed in this project suggest that this efflux pump might have an essential role in C. difficile physiology, possibly by serving as an efflux pump for toxic metabolites.
Keywords: Clostridium difficile; Efflux pump; TolC; Gram-positive; Resistance Nodulation Division